Nickel (II) complexes of polyhydroxybenzaldehyde N4-thiosemicarbazones: synthesis, structural characterization and antimicrobial activities - Shawish, H.B.; Paydar, M.; Looi, C.Y.; Wong, Y.L.; Movahed, E.; Halim, S.N.A.; Wong, W.F.; Mustafa, Mohd Rais; Maah, M.J. (2014)
Nickel(II) complexes with 2,3-dihydroxybenzaldehyde N4-substituted thiosemicarbazone ligands (H3L1âH3L4) have been synthesized and characterized with the aim of evaluating the effect of N4 substitution in the thiosemicarbazone moiety on their coordination behavior and biological activities. Two series of nickel(II) complexes with the general formulae Ni(H3L)(H2L)ClO4 and Ni2(HL)2 were characterized by analytical and spectral techniques. The molecular structure of one of the complexes, namely, Ni(H3L4)(H2L4)ClO4 was established by single crystal X-ray diffraction studies. The crystal structure of this complex revealed that two H3L4 ligands are coordinated to nickel(II) in different modes; one as a neutral tridentate ONS ligand and the other is as a monoanionic tridentate (ONSâ) ligand. The antimicrobial activities of the compounds were tested against 25 bacterial strains via the disc diffusion method, and their minimum inhibitory concentration (MIC) and minimum microbicidal concentration were evaluated using microdilution methods. With a few exceptions, most of the compounds exhibited low-to-moderate inhibitory activities against the tested bacterial strains. However, the complexes Ni2(HL3)2 (7) and Ni2(HL4)2 (8) indicated higher inhibitory activity against Salmonella enterica ATCC 9068 (MIC values 15.7 and <15.7 Î¼g/ml, respectively), compared with gentamicin as the positive control (MIC 25 Î¼g/ml). Complex (7) also inhibited Streptococcus pneumoniae more efficiently (MIC 31.2 Î¼g/ml), compared with gentamicin (MIC > 50 Î¼g/ml). The toxicities of the compounds were tested on brine shrimp (Artemia salina), where no meaningful toxicity level was noted for both the free ligands and the complexes. The cytotoxicities of the compounds on cell viability were determined on MCF7, PC3, A375, and H413 cancer cells in terms of IC50; complexes Ni(H3L3)(H2L3)ClO4 (3), Ni2(HL3)2 (7) and Ni2(HL4)2 (8) exhibited significant cytotoxicity on the tested cell lines.